Social Stratification, Ethnicity and Ethnical Economies (on the Example of Russia) - ФирсовЕвгений Юрьевич (Journal of Economic Sociology, 2010)
The aim of this paper is to find out whether neglecting of the ethnical diversity leads to the distortion of the real stratification of Russian society. Firstly the author solves the problem of the interaction of the ethnology and sociology in their analytical procedures and terminology. After that the stratification analysis of defined groups is given. The difficulty here is that main sociological theories were worked out by the western scientists with regard to their societies. The short review of the ethnical entrepreneurship in Europe and the USA allows us to define the frame for the Russian practices. The last two parts of the paper are devoted to the consideration of the Russian literature and to the design the own theory of ethnicity and stratification correlation. At the same time the author continuously addresses to the problem of importing the accumulated western knowledge to the analysis of Russian reality.